A new Permagrionidae from the Middle Permian of the South of France (Odonatoptera: Protozygoptera) - Fate, Caitlin; Lapeyrie, Jean; Nel, Andre (Zootaxa, 2013)
The new permagrionid protozygopteran genus and species Salagoulestes wesleyi is described from the Middle Permian of Lodève Basin, Salagou Formation. It seems to be more closely related to the two genera Scytolestes and Permagrion than to any other Permagrionidae. It increases the diversity of the odonatopteran fauna in the Salagou Formation to 14 different species.